L’expansion contemporaine du pentecôtisme en Amérique latine : une lecture en termes de champ - Jean-Pierre Bastian (Caravelle)
How may we report the religious diversification mainly through Pentecostalisms in Latin America by trying to construct the logics that underlie it ? The concept of religious field, elaborated by Bourdieu, permits to locate the actors in an investment logic whose stakes and challenges meet a specific interest, the mastery of the field’s reproduction by searching for symbolic and practical hegemony. Therefore, this paper doesn’t aim at describing all of the actors, but at thinking about a configuration of objective relations between positions held by diversified religious actors, relations which are determined by a main challenge which is the object of a war among competing organisations, in this case, the exercice of legitimate religious power in the region.